Diagnóstico de salud bucodental y factores de riesgo en el Centro Educativo Colegio de Bachillerato Rafael Rodríguez Palacios, de la parroquia rural Malacatos, del cantón Loja, año 2013 - Proaño Fernández, Julissa Beatriz (2013)
The pathologies of the oral cavity is a public health problem, because until now not possible to eradicate, which are influenced by factors that modify the state of health or disease in the population. The objectives of this research work were diagnosing diseases encountered , risk factors , and prevalence of these diseases , in Baccalaureate College students " Rafael Rodríguez Palacios" , parish Cato Malacatos of Loja , the sample was 120 students, for obtaining a survey data used in the same way that was filled written by students and dental history which recorded the clinically found where dental caries and gingival inflammation pathologies are greatest within sample and these were influenced by improper brushing technique , the infrequency of brushing and visiting the dentist low . After completing the study it can be concluded that there is a high rate of abnormalities of the oral cavity, the same that adversely affect the general health of the population, and that undoubtedly affects the person’s own development and the community together. As recommended prevention advocacy and oral, the population most at risk. KEYWORDS: oral health diagnosis, decay, gingival inflammation